Implementasi Metode Composite Performance Index (CPI) Pada Sistem Pendukung Keputusan Pemilihan SSD Eksternal - Nurhasan Nugroho (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The need for data storage is currently increasing, so external or portable data storage is developing. Likewise for SSDs, currently the External SSD market has been circulating which offers practicality, speed and large capacity. However, problems arise in selecting an External SSD, it will take time and effort to find information about product specifications and match the wishes and needs of the buyer. The purpose of this study is to implement the Composite Performance Index (CPI) method in a decision support system for choosing an External SSD, so that it can make it easier for users to determine alternatives quickly and precisely. The CPI method is used to solve decision problems with a number of alternatives through a combined index to rank alternatives from several criteria. The results of the calculations in the case study produced the highest score obtained by the alternative Kingston XS2000 SSD (A3) with a value of 130,001, followed by Lacie Rugged SSD Pro (A1) with a value of 108,334, Samsung SSD T7 Touch (A4) with a value of 100 and Seagate SSD Portable (A2) with a score of 93,335. The calculation of the CPI method obtained from the system obtains the same calculation results as the manual results. Based on testing with the black-box testing technique, all test cases are declared valid, this means that the system can work properly.